2014
DOI: 10.1017/jfm.2014.159
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of internal tides by irregular bathymetry of large extent

Abstract: We present an analytical theory of scattering of tide-generated internal gravity waves in a continuously stratified ocean with a randomly rough seabed. Based on a linearized approximation, the idealized case of constant mean sea depth and Brunt–Väisälä frequency is considered. The depth fluctuation is assumed to be a stationary random function of space, characterized by small amplitude and a correlation length comparable to the typical wavelength. For both one- and two-dimensional topographies the effects of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…One motivation to this study is the possibility to capture and predict processes that affect the propagation of the internal tides—such as topographic scattering—for example, for the construction of accurate parameterization of the associated mixing for general circulation models (Eden & Olbers, 2014; Lavergne et al., 2020; MacKinnon et al., 2017). Analytical expectations have been derived using different approaches and assumptions (Buhler & Holmes‐Cerfon, 2011; Y. Li & Mei, 2014), showing that the energy density of a given mode follows an exponential decay when passing over topographic irregularities with given statistical properties. The typical decay length scale λ depends on the latter: for instance Buhler and Holmes‐Cerfon (2011) obtained the following equality (their Equation 5.4) λ1=πnormalΓ02H2E|h|2E|h|2, where h is the topographic deviation from the mean value H and h its (one‐dimensional) gradient.…”
Section: Discussionmentioning
confidence: 99%
“…One motivation to this study is the possibility to capture and predict processes that affect the propagation of the internal tides—such as topographic scattering—for example, for the construction of accurate parameterization of the associated mixing for general circulation models (Eden & Olbers, 2014; Lavergne et al., 2020; MacKinnon et al., 2017). Analytical expectations have been derived using different approaches and assumptions (Buhler & Holmes‐Cerfon, 2011; Y. Li & Mei, 2014), showing that the energy density of a given mode follows an exponential decay when passing over topographic irregularities with given statistical properties. The typical decay length scale λ depends on the latter: for instance Buhler and Holmes‐Cerfon (2011) obtained the following equality (their Equation 5.4) λ1=πnormalΓ02H2E|h|2E|h|2, where h is the topographic deviation from the mean value H and h its (one‐dimensional) gradient.…”
Section: Discussionmentioning
confidence: 99%
“…As Melet et al (2013) found this fraction to vary regionally, global calculations of internal tide generation as well as subsequent breaking and Resolving the horizontal direction of internal tide generation 403 mixing might rely on including a spectral model like that of Goff & Jordan (1988) for the small-scale roughness (e.g. Goff & Arbic 2010;Li & Mei 2014;Guo & Holmes-Cerfon 2016), noting, however, that such models involve further uncertainties themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The scarcity of statistical theories may be due to the fact that information such as the wavenumber spectra of sea bathymetry is readily available only for some ocean basins ( [3], [15]). Such information has been only recently used in the studies of long-lasting tides and internal waves ( [4], [28]), but not yet applied to tsunamis.…”
Section: Introductionmentioning
confidence: 99%